2001
DOI: 10.1053/joca.2000.0373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a biomaterial with cartilage-like properties expressing type X collagen generated in vitro using neonatal porcine articular and growth plate chondrocytes

Abstract: These studies demonstrate the production in vitro of cartilage-like tissue with similar morphological, histochemical and biochemical characteristics to those of natural growth plate cartilage. The cartilage generated in vitro has the potential to be used in reconstructive surgery and in joint resurfacing and restoration of skeletal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The scaffold-free approach has previously been used to generate cartilaginous grafts using chondrocytes, BM-and synovial membrane-derived MSCs. 39,40,43,46,62 Furthermore, it has been demonstrated that such scaffold-free transwell cultures provide conditions FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffold-free approach has previously been used to generate cartilaginous grafts using chondrocytes, BM-and synovial membrane-derived MSCs. 39,40,43,46,62 Furthermore, it has been demonstrated that such scaffold-free transwell cultures provide conditions FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, this method has been used to engineer cartilaginous grafts from multiple different cell sources [39][40][41][42][43][44][45] and to engineer tissues of scale with healthy chondrocytes. 46,47 It is therefore also hypothesized that diseased FPSCs can be used to engineer cartilaginous grafts of clinically relevant dimensions ( > 2 cm) for the osteoarthritic patient population using such a scaffold-free or self-assembly approach.…”
Section: Introductionmentioning
confidence: 99%
“…The band obtained correlates with data presented in the literature for collagen type II protein. 36,37 Given the mesenchymal progenitor origin of BMC9 cells, which have not been shown to normally express collagen type II, this result leads us to believe that the cells were actually being directed toward the chondrogenic lineage. As a preliminary screening, such suggestions are indeed important for the future application of these systems in cartilage regeneration approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The band obtained correlates with data presented in the literature for collagen type II protein. 36,37 …”
mentioning
confidence: 99%
“…18,19 This has motivated research into scaffold-free techniques as a potential method for generating functional cartilage tissue. One of the first reported uses of a scaffold-free or selfassembly (SA) (or self-aggregating) approach for engineering cartilage-like tissue involved directly seeding chondrocytes onto plastic dishes precoated with poly(2-hydroxyethyl methacrylate), [20][21][22][23][24] which leads to the development of a graft with a hyaline cartilage phenotype in terms of the expression of collagen type II and aggrecan. 22 Alternative SA approaches involve aliquoting chondrocytes into an agarose mold or similar, and allowing these cells to self-assemble over time.…”
mentioning
confidence: 99%